Matrix association effects on hydrodynamic sorting and degradation of terrestrial organic matter during cross‐shelf transport in the Laptev and East Siberian shelf seas. Issue 3 (3rd March 2016) - Tesi, Tommaso; Semiletov, Igor; Dudarev, Oleg; Andersson, August; Gustafsson, Örjan
Abstract: This study seeks an improved understanding of how matrix association affects the redistribution and degradation of terrigenous organic carbon (TerrOC) during cross‐shelf transport in the Siberian margin. Sediments were collected at increasing distance from two river outlets (Lena and Kolyma Rivers) and one coastal region affected by erosion. Samples were fractionated according to density, size, and settling velocity. The chemical composition in each fraction was characterized using elemental analyses and terrigenous biomarkers. In addition, a dual‐carbon‐isotope mixing model (δ 13 C and Δ 14 C) was used to quantify the relative TerrOC contributions from active layer (Topsoil) and Pleistocene Ice Complex Deposits (ICD). Results indicate that physical properties of particles exert first‐order control on the redistribution of different TerrOC pools. Because of its coarse nature, plant debris is hydraulically retained in the coastal region. With increasing distance from the coast, the OC is mainly associated with fine/ultrafine mineral particles. Furthermore, biomarkers indicate that the selective transport of fine‐grained sediment results in mobilizing high‐molecular weight (HMW) lipid‐rich, diagenetically altered TerrOC while lignin‐rich, less degraded TerrOC is retained near the coast. The loading (µg/m 2 ) of lignin and HMW wax lipids on the fine/ultrafine fraction drastically decreases with increasing distance from the coast (98% and 90%, respectively), which indicates extensive degradation during cross‐shelf transport. Topsoil‐C degrades more readily (90 ± 3.5%) compared to the ICD‐C (60 ± 11%) during transport. Altogether, our results indicate that TerrOC is highly reactive and its accelerated remobilization from thawing permafrost followed by cross‐shelf transport will likely represent a positive feedback to climate warming. Key Points: Sorting exerts first‐order control on redistribution of carbon pools over the Siberian margin Plant debris accumulates inshore while mineral‐bound OC is transported offshore Terrestrial organic matter is susceptible to intense degradation during cross‐shelf transport